The Probable Association between Chronic Toxoplasma gondii Infection and Type 1 and Type 2 Diabetes Mellitus: A Case-Control Study - Soltani, Shahrzad; Tavakoli, Sanaz; Sabaghan, Mohamad; Kahvaz, Mehdi Sagha; Pashmforosh, Marzieh; Foroutan, Masoud (Interdisciplinary Perspectives on Infectious Diseases, 2021)
Purpose. The probable association between Toxoplasma gondii (T. gondii) infection and diabetes mellitus (DM) is still controversial, and there are several studies with conflicting results. Thus, this study was performed to assess the possible association between chronic T. gondii infection and type 1 diabetes mellitus (T1DM) and T2DM. Methods. In this case-control study, a total of 105 diabetic subjects including 36 patients with T1DM and 69 patients with T2DM were recruited. In addition, 150 nondiabetic subjects were enrolled as controls. Each case group had its own control group. Each participant completed a structured questionnaire obtaining demographic information. Serum samples were examined for T. gondii-specific IgG antibody using enzyme-linked immunosorbent assay (ELISA) method. Results. Analysis revealed that 69.4% and 34.0% of patients with T1DM and control subjects were serologically positive for T. gondii, respectively (odds ratio (OR): 4.41; 95% confidence interval (CI): 1.75–11.06; P=0.001). Moreover, 72.5% of T2DM patients and 29.0% of healthy individuals were seropositive for T. gondii (OR: 6.44; 95% CI: 3.25–12.74; P<0.001). Among risk factors, only contact with cats was significantly associated with IgG seroprevalence in both T2DM patients (P<0.001) and control subjects (P=0.045). Conclusion. Although the results showed that chronic T. gondii infection is significantly associated with T1DM and T2DM, there remain many questions regarding the exact mechanisms of T. gondii in the pathogenesis of DM.